Study Of Led Retrofit Lamps In Hspv Luminaires Based On Photometric Method For Road Lighting - Mohd Hanif Jamaludin; Wan Zakiah Wan Ismail; Elina Mohd Husini; Nor Ain Mohd Bahror (UPM, 2024)
Indexed by WOS/ Scopus